Structural Modeling of Food Safety Knowledge, Attitude, and Practices of Food Handlers in Highway Tourist Stop-Over Food Service Establishments in Uganda - Mukama, Innocent Hope Tinka; Mukisa, Mukisa; Charles Kyeyune, Muyanja (ASEAN Journal on Hospitality and Tourism, 2024)
The study examines the socio-demographic characteristics, food safety knowledge, attitudes, and practices of food handlers in highway tourist stop-over food service establishments in Uganda. The study further explores the relationship between the above factors using the Structural Equation Model (SEM). Understanding food safety knowledge, attitudes, and practices of food handlers can inform future interventions toward food safety assurance in food service establishments. The study used a cross-sectional design and data was collected using a self-administered structured questionnaire. Data was analyzed using Statistical Package for Social Sciences (SPSS) Version 22 and Analysis of Moment Structures (AMOS). Approximately half of the respondents had adequate knowledge of food safety and good practices. The results from SEM confirmed that food safety knowledge significantly affected practices (β= 0.37 p<0.05), attitude insignificantly, and negatively affected practices (β= -0.04 p>0.05). Only 13.3% of the changes in practices were explained by the knowledge and attitudes of the respondents (R-squared 0.133). The majority of the food handlers were males, had experience of more than 2 years, attended food safety training, and had limited knowledge about Hazard Analysis Critical Control Points (HACCP). The study is the first of its kind in Uganda. The findings suggest that future interventions should look beyond food safety knowledge and attitudes of the food handlers in food safety assurance efforts.